Diabetic Foot Detector - Mohd Hanafi bin Mustaffa, Mohd Hanafi (2010)
Diabetic foot detector is a device use to detect human foot pressure especially for diabetic patient. The abnormality of the foot pressure is an early indication of the diabetic foot. Diabetic patient with this symptom cannot control the pressure applied to the feet resulting tissue injury to the foot even for a short distance walking.